If the solve the problem


If $y=\sin (\sin x)$, prove that $: \frac{d^{2} y}{d x^{2}}+\tan x \cdot \frac{d y}{d x}+y \cos ^{2} x=0$



$y=\sin (\sin x) \ldots \ldots .$ equation 1

To prove: $\frac{\mathrm{d}^{2} \mathrm{y}}{\mathrm{dx}^{2}}+\tan \mathrm{x} \cdot \frac{\mathrm{dy}}{\mathrm{dx}}+\mathrm{y} \cos ^{2} \mathrm{x}=0$

We notice a second-order derivative in the expression to be proved so first take the step to find the second order derivative.

Let's find $\frac{d^{2} y}{d x^{2}}$

As $\frac{d^{2} y}{d x^{2}}=\frac{d}{d x}\left(\frac{d y}{d x}\right)$

So, lets first find $\mathrm{dy} / \mathrm{dx}$

$\frac{d y}{d x}=\frac{d}{d x} \sin (\sin x)$

Using chain rule, we will differentiate the above expression

Let $t=\sin x \Longrightarrow \frac{d t}{d x}=\cos x$

$\frac{\mathrm{dy}}{\mathrm{dx}}=\frac{\mathrm{dy}}{\mathrm{dt}} \frac{\mathrm{dt}}{\mathrm{dx}}$

$\frac{d y}{d x}=\cos t \cos x=\cos (\sin x) \cos x \ldots \ldots .$ equation 2

Again differentiating with respect to $x$ applying product rule:

$\frac{d^{2} y}{d x^{2}}=\cos x \frac{d}{d x} \cos (\sin x)+\cos (\sin x) \frac{d}{d x} \cos x$

Using chain rule again in the next step-

$\frac{d^{2} y}{d x^{2}}=-\cos x \cos x \sin (\sin x)-\sin x \cos (\sin x)$

$\frac{d^{2} y}{d x^{2}}=-y \cos ^{2} x-\tan x \cos x \cos (\sin x)$

[using equation $1: y=\sin (\sin x)$ ]

And using equation 2, we have:

$\frac{\mathrm{d}^{2} \mathrm{y}}{\mathrm{dx}^{2}}=-y \cos ^{2} \mathrm{x}-\tan \mathrm{x} \frac{\mathrm{dy}}{\mathrm{dx}}$

$\frac{\mathrm{d}^{2} \mathrm{y}}{\mathrm{dx}^{2}}+\mathrm{y} \cos ^{2} \mathrm{x}+\tan \mathrm{x} \frac{\mathrm{dy}}{\mathrm{dx}}=0 \ldots \ldots .$ proved

Leave a comment


Click here to get exam-ready with eSaral

For making your preparation journey smoother of JEE, NEET and Class 8 to 10, grab our app now.

Download Now